Dynamic Model for Assessing 222Rn and Progeny Exposure from Showering with Radon-Bearing Water - Datye, V. K; Hopke, P. K; Fitzgerald, B; Raunemaa, T. M (Environmental science & technology, 1997)
In homes supplied by water with a high radon content, inhalation exposure from the radon in the water may occur on two different time scales:  (a) long-term exposure that occurs due to an increase in the background radon concentration from radon released during water use and (b) short-term exposure that occurs during actual radon use such as in the bath, kitchen, and laundry room. While the former mode has been the subject of several studies, not much is known about the latter mode of exposure. During water use, the radon concentration can be considerably higher than the background and varies rapidly with time. Most of the exposure occurs well before a steady state can be reached. The goal of this work was to develop a dynamic, size-dependent model for the radon progeny activity during showering. The model includes radon and progeny decay, attachment of progeny to the existing aerosol, recoil, ventilation, and surface deposition. The model is used to evaluate radon exposure during and subsequent to showering as a function of environmental and other parameters (such as aerosol profile, bathroom dimensions, ventilation rate, and shower duration). These results are used in conjunction with a recent dosimetric model to obtain the integrated lung dose as a function of time.